2022
DOI: 10.1186/s12890-022-02168-8
|View full text |Cite
|
Sign up to set email alerts
|

Clinical benefits of inhaled ciclesonide for hospitalized patients with COVID-19 infection: a retrospective study

Abstract: Background The successful management of patients infected with coronavirus disease 2019 (COVID-19) with inhaled ciclesonide has been reported, however few studies have investigated its application among hospitalized patients. Methods This retrospective cohort study enrolled all adult patients admitted to our hospital with confirmed COVID-19 infection from May to June 2021. Critical patients who received mechanical ventilation within 24 h after admi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 57 publications
0
1
0
Order By: Relevance
“…Sixth, we used systemic steroid administration within 2 days of admission in our analysis. We did not exclude systemic steroids from our analysis because a previous retrospective study showed that systemic steroids were not associated with in-hospital mortality rates in non–severely ill hospitalized patients with COVID-19 [ 32 ]. However, the use of this factor in analysis may have influenced our results.…”
Section: Discussionmentioning
confidence: 99%
“…Sixth, we used systemic steroid administration within 2 days of admission in our analysis. We did not exclude systemic steroids from our analysis because a previous retrospective study showed that systemic steroids were not associated with in-hospital mortality rates in non–severely ill hospitalized patients with COVID-19 [ 32 ]. However, the use of this factor in analysis may have influenced our results.…”
Section: Discussionmentioning
confidence: 99%